Root‐zone management practices impact above and belowground growth in Cabernet Franc grapevines. (7th October 2015) - Centinari, M.; Vanden Heuvel, J.E.; Goebel, M.; Smith, M.S.; Bauerle, T.L.
Abstract: Background and Aims: The objective of this study was to assess the effect of root pruning (RP) and annual under‐trellis cover crops (UTCC) on vegetative growth and physiological processes in Cabernet Franc ( V itis vinifera L.) grapevines grafted on 3309C rootstock. Methods and Results: Five root‐zone management treatments, namely under‐trellis vegetation‐free strip control (C), RP and three distinct annual UTCC [annual ryegrass (AR), buckwheat, (BW) and turnip (TP)] were evaluated and compared over three seasons in a vigorous vineyard in the Northeastern USA. Root pruning had the greatest impact in reducing grapevine size; AR reduced the duration of shoot growth 2 out of 3 years. Competition between grapevine and AR and BW fine roots resulted in a lower grapevine fine root production in shallow soil layers and in a decrease in fine root lifespan. Conclusions: Root pruning was effective in reducing grapevine size for 3 years; RP effectiveness, however, may vary greatly depending on site conditions. Annual UTCC hold potential for reducing grapevine size in vigorous plantings in regions with ample precipitation. Appropriate choice of cover crop species, however, remains unclear. Significance of the Study: This work demonstrates that root‐zone management practices impact grapevine vegetative growth and induce changes in root morphological traits.